BRCA1 epigenetic inactivation predicts sensitivity to platinum-based chemotherapy in breast and ovarian cancer - Stefansson, Olafur A. (Landes Bioscience, 2012)
Germline mutations in the BRCA1 or BRCA2 genes are associated with an increased risk of breast and ovarian cancer development. Both genes are involved in DNA repair, and tumors harboring genetic defects in them are thought to be more sensitive to DNA-damaging agents used in chemotherapy. However, as only a minority of breast and ovarian cancer patients carry BRCA1 or BRCA2 mutations, few patients are likely to benefit from these pharmacogenetic biomarkers. Herein, we show that, in cancer cell lines and xenografted tumors, BRCA1 CpG island promoter hypermethylation-associated silencing also predicts enhanced sensitivity to platinum-derived drugs to the same extent as BRCA1 mutations. Most importantly, BRCA1 hypermethylation proves to be a predictor of longer time to relapse and improved overall survival in ovarian cancer patients undergoing chemotherapy with cisplatin.